Integrasi Tasawuf dan Modernitas dalam Pendidikan Islam Prespektif Fethullah Gulen - Apap Nazihah; Ilham Habibi Maulana (Tafkir: Interdisciplinary Journal of Islamic Education, 2020)
Indonesia is the biggest Muslim population in the world. The process of Islamization in this country is not through territorial conquest but among the biggest factors is through Sufism and education. One of the teachings of Sufism that developed at this time is the teachings of Sufism Fethullah Gulen. The purpose of this study is to reveal the ideal Islamic education system design and implementation according to Fethullah Gulen. Through manevi and hizmet activities, Gulen designed an education system that combines aspects of Sufism and modernity. This education system is considered successful in forming students so that they have competence in both intellectual and moral aspects.